Hyperxiphia hirashimai, comb. n. (Hymenoptera, Xiphydriidae) from southern Japan: remarkable sexual dimorphism revealed by DNA barcodes and new distribution records - Shinohara, Akihiko; Yamasako, Junsuke (Zootaxa, 2020)
Based on a study of the type material, Genaxiphia hirashimai Okutani, 1965, a southern Japanese xiphydriid showing remarkable sexual dimorphism, is newly combined with the genus Hyperxiphia Maa, 1949. The previously unknown female is described, and the male is redescribed with additional material. The sexes are associated by examination of specimens of both sexes that apparently emerged from the same piece of branch and by a molecular analysis using mitochondrial COI sequences. Hyperxiphia hirashimai, originally described from Amami-oshima Island, is newly recorded from Miyake-jima Island, southwestern Shikoku, southern Kyushu, Yakushima, Kuroshima and Okinawa-jima Islands.